The use of bilateral ТАР-block in open abdominal operations - Tokar, I. A.; Artjomenko, V. U. (Pain medicine, 2016)
The article describes the methodology of the bilateral TAPblock in abdominal laparotomy access in patients with cancer and severy comorbidies.